Strategi pengembangan Desa Layak Anak untuk pemenuhan hak anak secara menyeluruh di Desa Sukawati - Seroja, Ni Putu Maharani Aswasukma; Yudartha, I Putu Dharmanu; Yasintha, Putu Nomy (CITIZEN CHARTER, 2022)
Sukawati Village is one of the child-friendly villages in Gianyar Regency. Childfriendly village development aims to respect, guarantee and fulfill children's rights and protect children. This research was analyzed using Wheelen and Hunger theory and SWOT analysis. The results of this study indicate that there are still problems related to the development of child-friendly village programs in Sukawati Village, where there is still a lack of socialization about work programs owned by the village government to the community, lack of balance between creativity programs and intellectual development programs, lack of facilities and infrastructure for children's play in schools. lack of involvement of the private sector in program development, lack of competent human resources in the field of technology. Keyword : Child Friendly Village, Sukawati Village, Strategic Management